Analysis on Arabic Language Learning Based on Digital Sparkol VideoScribe in MI Nurus Sholah Pamekasan Students: Analisis Pembelajaran Bahasa Arab Berbasis Digital Sparkol VideoScribe pada Siswa MI Nurus Sholah Pamekasan - Azhari, Jalaludin; Jannah, Raudlatul; Asyhari, Asyhari (Madrosatuna: Journal of Islamic Elementary School, 2024)
In line with advances in telecommunications technology such as computer networks, software, and hardware, technological developments have accelerated very rapidly in the last few decades. This research was conducted to analysis on Arabic language learning based on digital sparkol videoscribe in MI Nurus Sholah Pamekasan students. A qualitative research approach was used in this study because the type of research used in this study was phenomenological, while the data that influenced the research results were descriptive. First, the application is so easy to obtain (how to acquire) and apply (how to use). Second, this application contains features that are so useful in the context of learning Arabic. Third, the application is familiar to students, so it is easy to recognize and understand. Fourth, the application of this Arabic learning application is able to support innovation in learning Arabic, reveal new insights, make self-learning more communicative, and then motivate everyone. The fifth contains the substance of the material content, which is represented in various visual, acoustic, and audiovisual formats with excellent color language capacity and object resolution